Analisis Kelayakan Potensi Objek Daya Tarik Wisata (ODTWA) Taman Wisata Alam Indah Lestari di Kabupaten Kubu Raya Kalimantan Barat - Liliyana; Hermina, Utin Nina; Anggita (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research is motivated by the post-COVID-19 development in the tourism industry, which has been striving to rebuild and enhance its performance. The objectives of this research are as follows: (1) to analyze the potential and various forms of natural tourist attractions found at Taman Wisata Alam Indah Lestari in Kubu Raya Regency, West Kalimantan; and (2) to identify and describe the strategic measures required to enhance the potential and development of these natural attractions within the area. The data collection was conducted through observation, interviews, and documentation. The results of this study indicate that there are five indicators categorized as highly suitable for development and two indicators categorized as moderately suitable or not yet ready for development. The potential of tourist attractions, with a score of 780 and a feasibility index of 86.66%, is classified as highly suitable for development. The accessibility potential, with a score of 275 and a feasibility index of 68.75%, is also categorized as highly suitable for development. The socio-economic environmental potential, which obtained a score of 700 and a feasibility index of 87.5%, is likewise considered highly suitable for development. In contrast, the accommodation potential, with a score of 60 and a feasibility index of 33.33%, is classified as moderately suitable and not yet ready for development. The clean water availability potential shows excellent results, with a score of 900 and a feasibility index of 100%, making it highly suitable for development. Meanwhile, the security potential, with a score of 250 and a feasibility index of 55.55%, is categorized as moderately suitable and not yet ready for development.